Immobilization of Captive Kulans (Equus hemionus kulan) Without Using Ultrapotent Opioids - Bohner, Julia; Painer, Johanna; Bakker, Denyse; Haw, Anna Jean; Rauch, Hanna; Greunz, Eva Maria; Egner, Beate; Goeritz, Frank (Frontiers in Veterinary Science, 2022)
Etorphine is widely used in zoological medicine for the immobilisation of large herbivores. All reported immobilisation protocols for kulans and other non-domestic equids use etorphine as the primary immobilizing agent. However, etorphine can trigger severe side effects, is highly toxic for humans and its availability is therefore occasionally limited for use in wildlife. Therefore, two different alpha-2 agonist-based protocols for the general anaesthesia of kulans were investigated and compared with the standard etorphine immobilisation. Twenty-one (21) immobilisations were performed within the scope of routine husbandry management at the Serengetipark Hodenhagen. Kulans were darted using either a ketamine-medetomidine-midazolam-butorphanol (KMMB) protocol (n = 8, Treatment Group (TG) 1), a zoletil-medetomidine-butorphanol (TZMB) protocol (n = 7, treatment group (TG) 2) or an etorphine-acepromazine-detomidine-butorphanol (EADB) protocol (n = 6, control group). Vital parameters included heart rate, respiratory rate, arterial blood pressures (invasively), electromyography and core body temperatures. These were all assessed every 10 minutes. For blood gas analysis arterial samples were collected 15, 30, 45 and 60 minutes after induction. Subjective measures of quality and efficacy included quality of induction, immobilisation, and recovery. Time to recumbency was longer for TG 1 (9.00 ± 1.67 minutes) and TG 2 (10.43 ± 1.79 minutes) compared to the shorter induction times in the control group (5.33 ± 1.93 minutes). Treatment group protocols resulted in excellent muscle relaxation, normoxemia and normocapnia. Lower pulse rates combined with systolic arterial hypertension was detected in both treatments groups. However, only in TZMB immobilised kulans sustained severe systolic arterial hypertension was observed, with significantly higher values compared to TG 1 and the normotensive control group. All three combinations provided smooth and rapid recoveries. To conclude, both the investigated treatment groups (KMMB and TZMB) provided a safe and efficient general anaesthesia in kulans with significantly better muscle relaxation, higher respiration rates and improved arterial oxygenation than the immobilisations of the control group. However, the control group (EADB) showed faster recoveries. Therefore, EADB is recommended for ultra-short immobilisations especially with free-ranging kulans where individual recovery is uncertain, whereas the investigated treatment groups are better for prolonged medical procedures on captive kulans.